ANTECEDENTS OF BANK PERFORMANCE THROUGH CUSTOMER JOURNEY INPRIVATE BANK - Denny Septa Haryanti; Bahtiar Usman; Sarfilianty Anggiani (Adisam Publisher, 2025)
This study aims to determine the role of Customer Journey as a variable in mediating Perceived Ease of Use, Perceived Risk and Intention to reuse self-service Technology towards Bank Performance to private bank customers. The analysis method used to answer the research problem using Structural Equation Modeling (SEM), where the data processing uses the Analysis of Moment Structures (AMOS) 24 program. The number of samples in this study was 226 respondents who were private bank customers. The results of this study found that in the Perceived Ease of Use hypothesis, Intention to Reuse Self Service Technology supports Bank Performance , and in the Perceived Ease of Use hypothesis, Perceived Risk and Intention to Reuse Self Service Technology also support Customer Journey . However, there is a hypothesis that does not support Perceived Risk which does not support Bank Performance. The novelty of this study lies in the discovery of the Customer Journey variable as a mediator that supports the hypothesis of Perceived Ease of Use, Perceived Usefulness, Perceived Risk and Intention to Reuse Self Service Technology towards Customer Journey .